Top Coal Weakening by Pulse Hydraulic Fracturing and Roof Cutting by Directional Hydraulic Fracturing for Control of Hanging Roof in the Face End of Fully Mechanized Top Coal Caving - Luying Shao; Bingxiang Huang; Xinglong Zhao; Haoze Li; Shuliang Chen (Lithosphere)
Due to the supporting effect of the coal pillar on the side of the roadway, there is often a problem of the top coal and roof in the working face end not collapsing in time. The single directional hydraulic fracturing method cannot directionally cut off the top coal of the working face end. To overcome the above shortcomings, this article first proposes a method of controlling top coal and roof in the working face end by pulse and directional hydraulic fracturing. The method of using pulse hydraulic fracturing to weaken the top coal and directional hydraulic fracturing to cut off the roof to induce rock pressure to break the coal is used to control the timely collapse of the top coal and roof in the working face end. When the vertical stress on the top coal is greater than the strength of the weakened top coal, the top coal and roof begin to collapse. The vertical displacement of the weakened top coal and the cut roof gradually decreases from low to high, and the caving top coal and roof finally fill the goaf. The maximum reduction in stress concentration of coal pillar is about 75%. Then, the principles for determining the parameters of this method were provided. Finally, the industrial experiment was conducted in the coal mine. The construction water pressure of the roof is between 30 and 40 MPa. The construction water pressure of top coal ranges from 8 to 16 MPa, with an amplitude of approximately 4 MPa. Directional crack is formed within an area of 3.3 m in the direction of the adjacent roof borehole. A crack network is formed within a 4 m area near the top coal borehole. After hydraulic fracturing, the top coal and roof in the working face end collapse with mining.